Quality of life in ovarian cancer survivors - Gonçalves, Vânia (2015)
Ovarian cancer survivors may experience Quality of Life (QOL) disruptions due to the aggressiveness of the illness and its treatment. The present manuscript intends to review the most recent knowledge regarding QOL in ovarian cancer survivors. Firstly, a brief overview about QOL, their importance and instruments used to assess it particularly in ovarian cancer survivors are presented. Then, main findings and developments achieved to date are discussed. Main conclusions from studies reviewed and future research needs are outlined. Available literature suggests that in general ovarian cancer survivors experience a good QOL; however, some deficits are more prevalent than in women without cancer. Although, these studies brought to light important QOL issues, more rigorous and larger studies are necessary to fully understand ovarian cancer survivors' QOL. Measuring QOL in ovarian cancer survivors in clinical settings is of utmost importance to identify those survivors at risk and provide adequate support that meets their needs.